Semantic retrieval : issues and motivation / Azilawati Azizan, Zainab Abu Bakar and Nurazzah Abd Rahman - Azizan, Azilawati; Abu Bakar, Zainab; Abd Rahman, Nurazzah (Universiti Teknologi MARA, Perak, 2018)
Currently, challenges in Information Retrieval are very closely related to the Semantic Web technology. Therefore, in this paper, we reported the current issue relating to semantic retrieval with main focus on ontology-based search. In order to support the presented issue, a retrieval evaluation on current semantic search engine was done to identify the current state of the retrieval performance on the Web. Several semantic search engines were selected and tested with a list of verified queries in the focused domain. The results showed that the precision of the retrieval still needs an improvement. Finally, based on existing publication and the demand from real-world applications, we proposed an initial conceptual framework for implementing semantic retrieval on the Web.